Keanekaragaman Kumbang Lucanid (Coleoptera:Lucanidae) Pada Berbagai Ketinggian Tempat di Hutan Konsensi Unocal Gunung Salak, Jawa Barat - Roni Koneri; Dedy Duryadi Solihin; Damayanti Buchori; Rudi Tarumingkeng (Institut Teknologi Bandung, 2010)
Lucanids beetles play a very important role in forest ecosystem and as an crucial element of biodiversity. The objectives of the research were to study the effects of different altitutdes on the community of lucanids beetles. Beetles collection was conducted by hand collection. Insect collections were conducted monthly during 12 months. This result identified 12 species of Lucanids beetles with 1.133 individuals. Altitude was found to have a strong effect on Lucanids beetles community. Redundancy analysis identified that total volume of coarse woody debris in the selected locations was recorded as key environmental factor influencing community structure of lucanids beetles. Based on canonical correspondence analysis, the distribution of the beetles were affected by the volume of coarse woody debris in decay class 2.